THE ROLE OF PERSONAL BRAND ON CONSUMER BEHAVIOUR IN TOURISM CONTEXTS: THE CASE OF MADEIRA - Bruno Sousa; Sónia Rodrigues (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2019)
In a world that undeniably competes for investment, visitors and residents, the adoption of approaches derived from the marketing has become a reality in the search for sustainability. It is a fact that a city marketing and brand management policy is able to promote and transform an image, boost economic activity and enhance all aspects of the city that present competitive advantage over other territories, so this is why associate marketing with cities makes sense. This study aims a better understanding of the brand image and their relationship with behavioural intentions, especially through the perceptions that tourists have toward the destinations (e.g. Madeira island), and how this may influence their attitudes. The objective of this study is to understand the impact of the personal brand on the image of a tourist destination, using as a case study the Madeira destination. An empirical study was carried out through questionnaires applied to 142 tourists in Madeira island. It was possible to understand the perception of visitors and assess the experience of visitors and the theoretical and practical contributions to local development and tourism marketing. Under an interdisciplinary perspective, this research brings together inputs from marketing, tourism and local economics. A theoretical model is developed specifying antecedents of satisfaction and loyalty in specific tourism contexts. Implications for future research are also presented.